2020
DOI: 10.1186/s12894-020-00637-y
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of three minimally invasive approaches for adrenal tumors: perioperative outcomes of transperitoneal laparoscopic, retroperitoneal laparoscopic and robot-assisted laparoscopic adrenalectomy

Abstract: Background To compare the perioperative outcomes of transperitoneal laparoscopic (TLA), retroperitoneal laparoscopic (RLA), and robot-assisted transperitoneal laparoscopic (RATLA) adrenalectomy for adrenal tumors in our center. Methods Between April 2012 and February 2018, 241 minimally invasive adrenalectomies were performed. Cases were categorized based on the minimally invasive adrenalectomy technique. Demographic characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
5
16
0
Order By: Relevance
“…Similarly to the majority of studies on this topic [23,24,34,[47][48][49][50][51][52][53][54], our experience confirms that robot-assisted adrenalectomy is a safe technique with acceptable perioperative complications rate.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly to the majority of studies on this topic [23,24,34,[47][48][49][50][51][52][53][54], our experience confirms that robot-assisted adrenalectomy is a safe technique with acceptable perioperative complications rate.…”
Section: Discussionsupporting
confidence: 84%
“…Most of the previous reports and meta-analysis exhibited similar results in terms of operative complications between these two approaches [24,[47][48][49][50][51][52][53][54]. Brandao et al [23] exhibited a not significant trend favoring robot-assisted adrenalectomy for postoperative complications in an analysis including 600 adrenalectomies performed mostly by the transperitoneal route (in 72.5% of robot-assisted and in 75.5% of laparoscopic adrenalectomy, respectively).…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, with increasing surgical experience and the improvements in laparoscopic instruments, tumor size is no longer an absolute contraindication to LRLA ( 15 ). Despite this, the retroperitoneum is a limited operative space, especially if the adrenal mass is large, making the procedure more challenging ( 16 ). Additionally, the limited retroperitoneal space can cause interference and collision of surgical instruments, increasing the difficulty of exposing and isolating the adrenal lesion ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description in 1992, 4 LA has been widely accepted due to its excellent clinical outcomes, and is currently regarded as the gold standard approach for the treatment of most adrenal tumors 5 . Recently, RAA was introduced as a potential alternative to LA to overcome some disadvantageous features of laparoscopic procedures, and there have been various studies showing superior findings of RAA to those of LA 6–13 . In fact, although LA remains more common than RAA in the United States, there is a clear trend toward increasing use of the robotic system in adrenalectomy 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Adrenalectomy for benign and malignant tumors is a complex surgical procedure, particularly in cases with large, malignant, and/or functioning tumors. Since the first report in 1992, 4 laparoscopic adrenalectomy (LA) has been widely accepted and is currently regarded as the gold standard procedure for most adrenal tumors, 5 while with recent progress in robotic surgery, robot‐assisted adrenalectomy (RAA) has been increasingly performed, and reported to achieve favorable perioperative outcomes in several previous studies 6–13 . For example, Agrusa et al conducted meta‐analysis and a systematic literature review focusing on adrenalectomy, and showed that RAA is a feasible surgical option, with reduced blood loss and short length of hospital stay compared with LA 8 …”
Section: Introductionmentioning
confidence: 99%